PERCEPTIONS OF HIGH SCHOOL STUDENTS IN EAST JAVA REGARDING IMPLEMENTATION SFH DURING THE COVID-19 PANDEMIC - Meisandy, Riyo Rosi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This study aims to comprehend: 1) the obstacles confronted by high school students in East Java in implementing study from home; 2) Readiness of learning facilities for high school students in East Java in undertakingÂ study from home; 3) The platform or application used for the implementation of study from home for high school students in East Java; 4) The advantages and disadvantages of implementing study from home for high school students in East Java. This study uses a descriptive method with a quantitative approach. In addition, primary data was obtained by using a questionnaire with google form in 354 student respondents from East Java. The result of this research was found that the biggest obstacles confronted by students in implementing study from home 46.3% were limited availability of internet access; 24.6% signal difficulty; 11.3% there are differences in the learning platforms used by each teacher. The level of readiness of students to confront study from home showed that 88.4% of students were ready because their cellphones or devices had supported the online learning. Platforms used for students in East Java to access online learning are: Whatsapp Group 70.6%;Zoom 5.1% and Google Classroom 4%. The advantages of implementing study from home are time efficiency, more diverse learning materials, flexible places to study, while the disadvantage of implementing study from home is that the technology used in learning is difficult and ineffective in teaching and learning activities.Â Keywords: Online learning; Students perception; Covid-19 pandemic